Integrated surgical management of neuroischemic diabetic foot syndrome, abdominal aortic aneurysm and renal artery lesionsin patients with diabetes mellitus type 2 - Sergey Anatol'evich Terekhin (Endocrinology Research Centre, 2011)
The article presents a clinical example of integrated surgical management in patient with multifocal atherosclerosis, chronic kidney disease andneuro-ischemic form of diabetic foot syndrome